A new water mite genus from Kazakhstan (Acari, Hydrachnidia, Hydryphantidae) - Tuzovskij, Petr V.; Stolbov, Vitaly A. (Zootaxa, 2021)
This paper describes a new genus of the water mite family Hydryphantidae. The material was collected by V. Stolbov in 2019 in running waters in Kazakhstan. The material was sampled with a common hand net with 250 µm mesh size. The water mites were fixed in 75% ethanol.